Deregulation of miR-183 and KIAA0101 in Aggressive and Malignant Pituitary Tumors - Roche, Magali; Wierinckx, Anne; Croze, Séverine; Rey, Catherine; Legras-Lachuer, Catherine; Morel, Anne-Pierre; Fusco, Alfredo; Raverot, Gérald; Trouillas, Jacqueline; Lachuer, Joel (Frontiers in Medicine, 2015)
Modulation of microRNAs (miRNAs) expression in many types of cancer suggests that they may be involved in crucial steps during tumour progression. Indeed, miRNAs deregulation has been described in pituitary tumourigenesis, but few studies described their role in pituitary tumour progression towards aggressiveness and malignancy. To assess the role of miRNA within the hierarchical events cascade occurring in prolactin (PRL) tumours during progression towards aggressiveness and malignancy, we used an integrative genomic approach associating clinic-pathological features, global miRNA expression and transcriptomic profiles performed on the same human tumours. We described the down-regulation of one principal miRNA, miR-183 specifically in the 8 aggressive (A, grade 2b) as compared to the 18 non-aggressive (NA, grades 1a, 2a) PRL tumours. We demonstrated that it acted as an anti-proliferative gene by directly targeting KIAA0101 which is involved in cell cycle activation and inhibition of p53-p21 mediated cell cycle arrest. Moreover, we showed that miR-183 and KIAA0101 expression are significantly correlated with the main markers of pituitary tumours aggressiveness Ki-67 and p53 labeling. These results confirmed the activation of proliferation in aggressive and malignant PRL tumours as compare to non-aggressive ones. Importantly, those data also demonstrate the ability of such an integrative genomic strategy, applied in the same human tumours, to identify the molecular mechanisms responsible for tumoural progression even from a small cohort of patients.